The Unstable Dialectic of Defiance: A Post-Structuralist Deconstruction of Rebellion Against Technology in Selected Dystopian Short Stories - Adinda (English Literature Department, Adab and Humanities Faculty, 2025)
The purpose of this study is to examine the issue of rebellion against technology in three short stories: Ray Bradbury's The Veldt (1950), E. M. Forster's The Machine Stops (1909), and Harlan Ellison's I Have No Mouth and I Must Scream (1967). Using a post-structuralist perspective, the study aims to deconstruct the meanings of rebellion against technology and explain its causes and effects. The theoretical framework uses Albert Camus's concept of rebellion (1951) to interpret existential resistance, Jacques Derrida's concept of deconstruction (1976) to analyze textual ambiguities, and Jacques Ellul's theory of technological determinism (1964) to comprehend the dominance of machines. The purpose of this study is to examine the issue of rebellion against technology in three short stories: Ray Bradbury's The Veldt (1950), E. M. Forster's The Machine Stops (1909), and Harlan Ellison's I Have No Mouth and I Must Scream (1967). Using a post-structuralist perspective, the study aims to deconstruct the meanings of rebellion against technology and explain its causes and effects. The theoretical framework uses Albert Camus's concept of rebellion (1951) to interpret existential resistance, Jacques Derrida's concept of deconstruction (1976) to analyze textual ambiguities, and Jacques Ellul's theory of technological determinism (1964) to comprehend the dominance of machines.